Pengaruh Pendidikan Kewirausahaan terhadap Minat Berwirausaha yang Dimediasi oleh Pola Pikir Kewirausahaan pada Siswa SMK YPE Sawunggalih Kutoarjo - Tafsir Komaria; Aniek Hindrayani; Dini Octoria (Departement of Mathematics Education, 2023)
This study aims to determine the effect of entrepreneurship education on entrepreneurial interest by including entrepreneurial mindset as a mediating variable. Quantitative descriptive methods are used to gain a clearer understanding of the relationship between variables using Structural Equation Modeling (SEM) based on Partial Least Square (PLS) variants. The research was conducted at SMK YPE Sawunggalih Kutoarjo with a population of 436 students and a sample of 209 students. Data were collected using an online questionnaire assisted by google forms. The findings of this study indicate that entrepreneurship education has a positive and significant effect on entrepreneurial interest and entrepreneurial mindset, then entrepreneurial mindset has a positive and significant effect on entrepreneurial interest. Finally, the existence of an entrepreneurial mindset is able to mediate the relationship between entrepreneurship education and entrepreneurial interest of vocational students.